SEBUAH KONTEMPLASI TENTANG KLASIFIKASI HAK-HAK ASASI MANUSIA (Jurnal Wawasan Yuridika, 2010)
Today, Human rights study is the most popular study object and attracts many scholars from other disciplines, and law science as well. One of focused human rights study fields is right which can be classified as a part of human rights, as the rights cannot be mentioned as fundamental rights. This writing gives an ideal classification of human rights so it can represent the definition of human rights as a universal, eternal, and natural concept. Rights classified as human rights are as follow: (1) right to live; (2) right to speak and express opinion; (3) right to freedom of assembly; (4) right to participate in government; (5) right to continue descent; (6) right to achieve prosperity; (7) right to achieve equal justice; (8) right to perform religious service; and (9) right to achieve equal position under the lawKeywords: Human Rights, Fundamental Rights, Constitution Law